SHOPPING MOTIVATION IN CONSUMER LOYALTY PROCESS - Ratih Puspita Kusumaningrum; Aulia Danibrata (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
This study aims to examine the influence of hedonic, utilitarian, and ethical motives in process of forming consumer loyalty. The design that used in this research were descriptive research and causality research, in which variables were measure with 5-point likert scale. The technique that used in this research is non-probability sampling with purposive sampling technique and used 221 respondents who fit the criteria. This research is processes by using Structural Equation Modeling – Partial Least Square. The results of this calculation show that hedonic shopping motivation, utilitarian shopping motivation, and ethical shopping motivation through perceived quality as mediating variable have an influence on repurchase intention.